Leadless pacing in a patient with superior vena cava syndrome undergoing lead extraction and percutaneous angioplasty. Issue 6 (June 2018) - Zucchelli, Giulio; Favilli, Elena; Viani, Stefano; Barletta, Valentina; Di Cori, Andrea; Segreti, Luca; Bongiorni, Maria Grazia
Abstract: Superior vena cava (SVC) syndrome is an uncommon but serious complication associated with chronic transvenous implanted leads. In the recent past, open-heart surgery combining lead extraction and epicardial implant was usually performed to reduce syndrome recurrences. We describe the case of a 78-year-old man successfully treated by percutaneous lead extraction associated with venous balloon angioplasty and reimplantation of leadless pacemaker. <Learning objective: Chronic vascular complications following lead implantation usually require surgical treatment, due to the need for subsequent epicardial implantation. Percutaneous lead extraction along with leadless pacing allowed effective non-surgical management of chronic complications of transvenous pacing.>